Clinical researchers: The relationship between the final degree project and future prospects for developing research tasks in the clinical setting - Julia L. Gutierrez-Arroyo; Alba Loras; Elvira Carbonell; Pia Gallego; Maria Victoria Ibañez; Maria Angeles Marques-Torrejon; Conrado Martinez-Cadenas (Educación Médica)
Introduction: Clinical research is vital for improving individuals' quality of life, yet many medical students find it complex and challenging. Therefore, it is essential to introduce research training programs early in undergraduate medical education to help students develop basic research skills. One example is the final degree project (FDP), which can be either experimental/research-based or a systematic review/clinical protocol. This study investigates medical students' perceptions of research FDPs based on effort and difficulty, as well as the associations between FDP-type election and the graduates' future interest in research. Methods: A cross-sectional analytical study was conducted with 87 medical graduates from Jaume I University of Castellon. Data were collected through surveys, and both descriptive and inferential analyses were performed. Results: A significant relationship was found between research in the graduates' routine and the intention to pursue a doctoral thesis, as well as between the graduates' choice of FDP topic as medical students (experimental or research-based vs. systematic review or clinical protocol) and future engagement in a doctoral thesis. As this is an observational study, we cannot establish causality in this relationship. No significant associations were found between routine research and hospital size, gender, or career motivation, except for a potential significance in the relationship between FDP topic choice and medical specialty. Conclusions: Our main findings suggest that medical graduates' perceptions of the complexity of research FDPs depend on their prior research experience. Therefore, it is crucial to provide more training in this area during undergraduate programs to prevent a lack of training from becoming a barrier to pursuing a research career. Resumen: Introducción: La investigación clínica es vital para mejorar la calidad de vida de las personas, pero muchos estudiantes de medicina la encuentran compleja y desafiante. Por lo tanto, es esencial introducir programas de formación en investigación en las primeras etapas de la educación médica de pregrado para ayudar a los estudiantes a desarrollar habilidades básicas de investigación. Un ejemplo es el proyecto final de grado (TFG), que puede ser experimental/basado en investigación o una revisión sistemática/protocolo clínico. Este estudio investiga las percepciones de los estudiantes de medicina sobre los TFG de investigación en función del esfuerzo y la dificultad, así como la asociación entre la elección del tipo de TFG y el interés futuro de los graduados en la investigación. Material y Métodos: Se realizó un estudio analítico transversal con 87 graduados en medicina por la Universidad Jaume I de Castellón. Los datos se recolectaron mediante encuestas y se realizaron análisis tanto descriptivos como inferenciales. Resultados: Se encontró una relación significativa entre la investigación en la rutina de los egresados y la intención de realizar una tesis doctoral, así como entre la elección del tema del TFG (investigación experimental o basada en revisión sistemática o protocolo clínico) por parte de los egresados en medicina y su futura participación en una tesis doctoral. Al tratarse de un estudio observacional, no se puede establecer causalidad en esta relación. No se encontraron asociaciones significativas entre la rutina de investigación y el tamaño del hospital, el género o la motivación profesional, excepto por una potencial significatividad en la relación entre la elección del tema del TFG y la especialidad médica. Conclusiones: Nuestros principales hallazgos sugieren que las percepciones de los graduados en medicina sobre la complejidad de la investigación dependen de su experiencia previa en TFGs de investigación. Por lo tanto, es crucial brindar más formación en esta área durante los programas de pregrado para evitar que la falta de capacitación se convierta en una barrera para perseguir una carrera investigadora.